Ablating all three retinoblastoma family members in mouse lung leads to neuroendocrine tumor formation - Lázaro, Sara (Oncotarget, 2016)
Lung cancer is a deadly disease with increasing cases diagnosed worldwide and still a very poor prognosis. While mutations in the retinoblastoma (RB1) tumor suppressor have been reported in lung cancer, mainly in small cell lung carcinoma, the tumor suppressive role of its relatives p107 and p130 is still a matter of debate. To begin to investigate the role of these two Rb family proteins in lung tumorigenesis, we have generated a conditional triple knockout mouse model (TKO) in which the three Rb family members can be inactivated in adult mice. We found that ablation of all three family members in the lung of mice induces tumorlets, benign neuroendocrine tumors that are remarkably similar to their human counterparts. Upon chemical carcinogenesis, DHPN and urethane accelerate tumor development; the TKO model displays increased sensitivity to DHPN, and urethane increases malignancy of tumors. All the tumors developing in TKO mice (spontaneous and chemically induced) have neuroendocrine features but do not progress to fully malignant tumors. Thus, loss of Rb and its family members confers partial tumor susceptibility in neuroendocrine lineages in the lungs of mice. Our data also imply the requirement of other oncogenic signaling pathways to achieve full transformation in neuroendocrine lung lesions mutant for the Rb family.